Morphology, mineralogy and surface chemistry of manganiferous oxisols near Graskop, Mpumalanga Province, South Africa - Dowding, Catherine Elaine (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric)--University of Stellenbosch, 2004.